2022
DOI: 10.1016/j.rechem.2021.100263
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenoxyacetamide derivatives as SARS-CoV-2 main protease inhibitor: In silico studies

Abstract: 2-Phenoxyacetamide group has been identified as one of markers in the discovery and development of SARS-CoV-2 antiviral agent through its main protease (M pro ) inhibition pathway. This study aims to study a series of 2-phenoxyacetamide derivatives using in silico method toward SARS-CoV-2 M pro as the protein target. The study was initiated by employing structure-based pharmacophore to virtually screen and to select the ligands, which have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…, 35); 197 (7); 183 (100); 135 (36); 106 (33); 92 (33); 65 (12); 32 (4). (20); 133 (13); 105 (13); 91 (15); 41 (4.5); 32 (10).…”
Section: -(4-chloro-2-isopropyl-5-methylphenoxy)-n-phenylacetamide (3bunclassified
See 2 more Smart Citations
“…, 35); 197 (7); 183 (100); 135 (36); 106 (33); 92 (33); 65 (12); 32 (4). (20); 133 (13); 105 (13); 91 (15); 41 (4.5); 32 (10).…”
Section: -(4-chloro-2-isopropyl-5-methylphenoxy)-n-phenylacetamide (3bunclassified
“…These compounds have garnered attention from researchers due to their diverse range of biological activities, including antiinflammatory effects, 13 anticancer properties, 14,10 analgesic effects, 8 antimicrobial properties, 9 and potential against SARS-CoV-2. 15 The herbicidal potential of N-phenyl-2-phenoxyacetamides was reported in the study by Wu et al, 16 demonstrating that these compounds may have significant phytotoxic potential. In that study, 13 compounds from the class of N-(2-fluoro-5-(3methyl-2,6-dioxo-4-(trifluoromethyl)-2,3-dihydropyrimidin-1(6H)-yl)phenyl)-2-phenoxy)acetamides were synthesized and evaluated for herbicidal activity.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, 4'-O-methylscutellarein binds the active site, sequestering the catalytic dyad. [20][21][22] In addition, both testosterone and progesterone are Mpro inhibitors. 23 Molecular modeling and simulation results also suggested that insect protease 1KJ0-7 and 2ERW-9 are promising candidates as antivirals against SARS-CoV-2, they do not possess any mutagenic and carcinogenic properties and appear safe for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Methylated derivatives of Scutellarein are potential inhibitors of Mpro. For example, 4'‐O‐methylscutellarein binds the active site, sequestering the catalytic dyad 20–22 . In addition, both testosterone and progesterone are Mpro inhibitors 23 .…”
Section: Introductionmentioning
confidence: 99%